Examining the Effect of Inquiry-Based Problem-Solving Activities on the Problem-Solving Skills of 60-72 Months Old Children - Erhan Alabay; Yeliz Dal Berberoğlu (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
The present study aims to examine the effect of inquiry-based problem-solving activities on 60-72 months old children’s problem-solving skills. In the study, the pretest-posttest control group experimental design which is among the quantitative research designs was used. The study group consists of a total of 26 pre-school children as 13 in the experimental and 13 in the control group. The inquiry-based problem-solving activities prepared by the researchers were applied to the experimental group as a total of 30 sessions for 10 weeks and three times a week. Demographic information form and Problem-Solving Skills Scale were used as data collection tools. As a result of the study, it was determined that the problem-solving skill scores of the children in the experimental group were statistically higher than the students in the control group. In other words, inquiry-based problem-solving activities positively affected the problem-solving skills of children.